2002
DOI: 10.1002/bies.10083
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of sexual development in the mushroom Coprinus cinereus

Abstract: Sexual development in the mushroom Coprinus cinereus is under the control of two mating type loci, A and B. When two haploid homokaryons with compatible alleles at both A and B loci are mated, the coordinated activities of A- and B-regulated pathways lead to formation of a mycelium termed the dikaryon, in which the two nuclei from the mating partners pair in each cell without fusing. The dikaryon is a prolonged mycelial stage that can be induced to develop a multicellular structure, the mushroom, under proper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(18 citation statements)
references
References 90 publications
1
14
0
Order By: Relevance
“…The NanoLuc system, in contrast, performed well in our system. NanoLuc will be useful in analyzing cis -elements in the many genes that have been cloned in the long history of studying the genetics of mushroom-forming basidiomycetes 27, 28 . For instance, cis - analyses of PriA 29 , a marker gene for early development of the fruiting body, whose UTR elements has been analyzed 30 , will be informative in helping to unravel some aspects of the mechanism of the onset of fruiting body development.…”
Section: Discussionmentioning
confidence: 99%
“…The NanoLuc system, in contrast, performed well in our system. NanoLuc will be useful in analyzing cis -elements in the many genes that have been cloned in the long history of studying the genetics of mushroom-forming basidiomycetes 27, 28 . For instance, cis - analyses of PriA 29 , a marker gene for early development of the fruiting body, whose UTR elements has been analyzed 30 , will be informative in helping to unravel some aspects of the mechanism of the onset of fruiting body development.…”
Section: Discussionmentioning
confidence: 99%
“…In C. cinerea and other Agaricomycetes, each encounter of two monokaryotic hyphae results in promiscuous cell-cell fusion irrespective of whether or not they are compatible at MAT (18, 89). However, for the development and maintenance of the dikaryon, nuclei of interacting partners must harbor different allelic versions of genes in at least one sublocus of both P/R and HD loci (18, 89–91).…”
Section: Breeding Systems In the Basidiomycotamentioning
confidence: 99%
“…However, for the development and maintenance of the dikaryon, nuclei of interacting partners must harbor different allelic versions of genes in at least one sublocus of both P/R and HD loci (18, 89–91). Classical genetic analyses of these semi-compatible interactions in C. cinerea and S. commune have shown that the P/R system is involved in events that follow hyphal fusion, namely in the reciprocal exchange and migration of nuclei and clamp cell fusion (Fig.…”
Section: Breeding Systems In the Basidiomycotamentioning
confidence: 99%
“…This system is only found in basidiomycetes because, unlike all other fungi studied so far, they possess two independent molecular determinants of mating type [17]. Sexual compatibility is usually determined at a first level by lipopetide pheromones and plasma membrane pheromone receptors that mediate cell-cell recognition, with the exception of some homobasidiomycetes (the lineage that includes the mushrooms) where fusion of homokaryotic hyphae is not restrained by pheromone-mediated interactions [2], [18]. After cell fusion, progression through the sexual cycle requires overcoming a second compatibility hurdle that relies on a heterodimeric homeodomain transcription factor (HD1/HD2), encoded by a pair of divergently transcribed, closely linked genes [3], [19][21].…”
Section: Introductionmentioning
confidence: 99%